2001
DOI: 10.4049/jimmunol.166.8.5183
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Airway Th2 Response After Allergen Challenge in Mice Deficient in CC Chemokine Receptor-2 (CCR2)

Abstract: To evaluate the role of CCR2 in allergic asthma, mutant mice deficient in CCR2 (CCR2−/−) and intact mice were sensitized with i.p. OVA with alum on days 0 and 7, and challenged by inhalation with nebulization of either OVA or saline. Airway hyperreactivity, measured by the methacholine-provoked increase in enhanced pause, was significantly increased (p < 0.05) in OVA-challenged CCR2−/− mutant mice, compared with comparably challenged CCR2+/+ mice. OVA-challenged CCR2−/− mutants also were also found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 52 publications
6
52
1
Order By: Relevance
“…Whereas the response of CCR4-deficient mice in an OVA-induced asthma model was similar to that of WT animals (37), studies neutralizing CCL22/macrophage-derived chemokine (38) or CCL17/ thymus and activation-regulated cytokine (39) showed that blocking either of these CCR4-specific ligands attenuated allergic airway disease development. Conflicting results have also been published in studies of mice deficient in CCR2, a ␤-chemokine receptor reported not to be critical for development of OVA-induced pulmonary inflammation (40), or to modulate the corresponding immune response (41), whereas neutralization of the CCR2 ligand CCL2/monocyte chemoattractant protein-1 was reported to diminish the inflammation drastically (42).…”
Section: Discussionmentioning
confidence: 61%
“…Whereas the response of CCR4-deficient mice in an OVA-induced asthma model was similar to that of WT animals (37), studies neutralizing CCL22/macrophage-derived chemokine (38) or CCL17/ thymus and activation-regulated cytokine (39) showed that blocking either of these CCR4-specific ligands attenuated allergic airway disease development. Conflicting results have also been published in studies of mice deficient in CCR2, a ␤-chemokine receptor reported not to be critical for development of OVA-induced pulmonary inflammation (40), or to modulate the corresponding immune response (41), whereas neutralization of the CCR2 ligand CCL2/monocyte chemoattractant protein-1 was reported to diminish the inflammation drastically (42).…”
Section: Discussionmentioning
confidence: 61%
“…However, the induction of the Th2 response is clearly more complex and persistent or enhanced Th2 responses have been reported in CCR2Ϫ/Ϫ mice. 33,41 Hence, Th1 responses may have a net greater sensitivity to CCR2 knockout, which is intriguing in view of our observation that unlike with PPD challenge, CD40 induction was not as impaired in CCR2Ϫ/Ϫ mice challenged with a Th2-eliciting Ag, SEA.…”
Section: Discussionmentioning
confidence: 65%
“…Monocyte chemotactic protein (MCP) family chemokines are believed to play particularly important roles in these disorders. This is based on the demonstration that MCP-1 is a potent stimulator of mast cell mediator release, T cell chemotaxis, basophil chemotaxis, and tissue fibrosis, which also enhances naive T cell acquisition of a Th2 cell phenotype (19,22). It is also based on the demonstration that MCP-1, acting via its major receptor, CCR2, is the major recruiter of macrophages at sites of allergic tissue inflammation (23) and that MCP-1, MCP-3, and MCP-4 are expressed in a exaggerated fashion in tissues from patients with asthma (20,21,24,25).…”
Section: Il-13-induced Chemokine Responses In the Lung: Role Of Ccr2 mentioning
confidence: 99%
“…Although in vitro characterizations would suggest that there is impressive redundancy in this system, examinations of a limited number of ligands in vivo have demonstrated that their production is organized in a coordinated manner and that their effector functions can be restricted to different stages of disease development and/or pathology (17,18,39,44). Thus, in vivo, a deficiency of an individual ligand or its receptor can cause striking alterations in tissue phenotype (16,19). An impressive finding in our study is the potent and rapid induction of MCP-1 and other MCP moieties by IL-13 in the murine lung.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation